2022
DOI: 10.5811/westjem.2021.11.54001
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medicine Virtual Conference Participants’ Engagement with Competing Activities

Abstract: Introduction: Residency didactic conferences transitioned to a virtual format during the COVID-19 pandemic. This format creates questions about effective educational practices, which depend on learner engagement. In this study we sought to characterize the competitive demands for learner attention during virtual didactics and to pilot methodology for future studies. Methods: This was a prospective, observational, cohort study of attendees at virtual didactics from a single emergency medicine residency, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…However, many felt that the move to remote communication led to a decreased sense of connection with peers and colleagues resulting in a mixed picture of overall engagement and effectiveness. Other studies have shown that residents have decreased engagement with lectures in the online format, and often attendees are engaging in increased non-lecture-related activities during lecture time including email, entertainment, self-care, social, or other personal activities [ 13 , 14 ]. While evidence-based techniques for increasing engagement such as team-based or case-based learning may help, these have not yet been studied in the virtual didactic environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, many felt that the move to remote communication led to a decreased sense of connection with peers and colleagues resulting in a mixed picture of overall engagement and effectiveness. Other studies have shown that residents have decreased engagement with lectures in the online format, and often attendees are engaging in increased non-lecture-related activities during lecture time including email, entertainment, self-care, social, or other personal activities [ 13 , 14 ]. While evidence-based techniques for increasing engagement such as team-based or case-based learning may help, these have not yet been studied in the virtual didactic environment.…”
Section: Discussionmentioning
confidence: 99%
“…In the human-computer interaction module, it is mainly necessary to consider the interaction between users and the system. It is necessary to design a set of interactive methods to connect users with the system and ensure that users can quickly and conveniently obtain the required information and learning materials [15]. The Unity engine is mainly used during this process, and programming uses the # language.…”
Section: Overall System Framework Designmentioning
confidence: 99%